O processo decisório no Direito Penal Brasileiro: os parâmetros da individualização da pena e o seu impacto na sociedade - Rodrigues, Carolina Pimentel Tavares (2022)
The present monography aims to examine the judges’ method and wide discretionary margin when applying the sentence to convicts, among the limits previously established by the criminal legislation. Initially, the concepts related to the constitutional principle of individualization of the sentence and the sentence itself are going to be presented. Afterwards, a demonstration of the procedure established by the legislation for the proper application of the sentence in the specific cases by the judges will be made. Finally, the problem behind this form of application of the sentence will be presented and analyzed, which, in fact, is often unfair, partial and standardized